THE TEKTOLOGY OF O.BOGDANOV AS A IDEA SOURSE OF THE PRAXEOLOGY OF T.KOTARBINSKY - Льовкіна, О. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
This article analyses the community of the tektology of A.Bogdanov and of the praxeology of T.Kotarbin’sky.